Absence of Endolymphatic Sac Ion Transport Proteins in Large Vestibular Aqueduct Syndrome—A Human Temporal Bone Study. Issue 10 (December 2020) - Eckhard, Andreas H.; Bächinger, David; Nadol, Joseph B.
Abstract : Hypothesis: Epithelial ion transport pathologies of the endolymphatic sac (ES) are associated with large vestibular aqueduct syndrome (LVAS). Background: LVAS is defined by the pathognomonic features of a widened bony vestibular aqueduct (VA) and an enlarged ES. The underlying cause of its associated cochleovestibular symptoms remains elusive. Disturbances in epithelial ion transport in the enlarged ES, affecting inner ear fluid regulation, were proposed as a possible pathophysiology. However, although respective epithelial ion transport pathologies have been demonstrated in the enlarged ES from transgenic LVAS mouse models, these pathologies have not been investigated in human LVAS cases. Methods: Histological and immunohistochemical analysis of the enlarged ES epithelium in postmortem temporal bones from two individuals with a clinical diagnosis of LVAS. Results: The enlarged ES epithelium demonstrated an overall atypical epithelial differentiation and a lack of the immunolocalization of signature ion transport proteins. Notably, in both cases, a rudimentary branch of the ES with a typically differentiated ES epithelium was present. Conclusions: The described cellular and molecular pathologies of the enlarged ES in humans provide evidence of epithelial transport pathology as one potential cause of cochleovestibular symptoms in LVAS. The present findings also emphasize the clinical relevance of already established LVAS mouse models.